Effects of Employees’ Attitudes towards Digital Transformation Factors on SMEs’ Sustainability and Financial Performance - Mihajlovic, Ivan; Spasojevic Brkic, Vesna; Perisic, Martina; Milosevic, Isidora; Arsic, Sanela (Transformations In Business & Economics, 2025)
Digital transformation is the most frequently analysed from the technological perspective. The following research investigates the social elements of organisational digital transformation, by placing employees in SMEs in focus. After extensive literature review the research questions and related hypotheses were defined. To test the proposed hypotheses, a questionnaire was developed, and 635 responses were received from individual owners, managers, and employees in organizations from Serbia, Bulgaria, and Visegrad Four countries (V4). A structural equation model has been used to explore the mediating effect on the relationship between the employee’s attitudes and their perceived opinions on the organisations’ sustainability and financial performance. All relationships within stated hypotheses were confirmed. It was revealed that employees’ positive attitude towards digitalisation is improving their self-efficacy in the digitalized work.